Copy number variations in a population with prune belly syndrome. Issue 11 (4th October 2018) - Iqbal, Nida S.; Jascur, Thomas A.; Harrison, Steven; Chen, Catherine; Arevalo, Michelle K.; Wong, Daniel; Sanchez, Emma; Grimsby, Gwen; Wilson, Kathleen; Baker, Linda A.
Abstract : Prune Belly Syndrome (PBS) is a congenital multisystem myopathy with mild to lethal severity. While of uncertain etiology, 95% male predominance and familial occurrence suggest a genetic basis. As copy number variations (CNVs) can cause unexplained genetic disorders, we tested for novel CNVs in a large PBS population. We genotyped 21 unrelated PBS patients by high‐resolution array comparative genomic hybridization (aCGH) and phenotyped using a novel PBS severity scoring system. Available parents were screened for detected CNV via quantitative PCR (qPCR). We additionally screened for recurrence of identified novel candidate CNVs on 106 PBS probands by qPCR. We identified 10 CNVs in 8 of 21 PBS patients tested (38%). Testing confirmed inheritance from an unaffected biological parent in six patients; parental samples were unavailable in two probands. One candidate CNV includes duplication of the X‐chromosome AGTR2 gene, known to function in urinary tract development. Subsequent screening of the larger PBS cohort did not identify any recurrent CNVs. Presence of CNV did not correlate with PBS severity scoring. CNVs were uncommon in this large PBS population, but analysis of identified variants may inform disease pathogenesis and reveal targets for therapeutic intervention for this rare, severe disorder.